A Review on Zeolite Application for Aromatic Production from Non-Petroleum Carbon-Based Resources - I. G. B. N. Makertihartha; Noerma Juli Azhari; Grandprix T.M. Kadja (Journal of Engineering and Technological Sciences, 2023)
The application of zeolite catalyst has been expanded to support on-purpose sustainable technology. This review focused on zeolite application to produce aromatic compounds from non-petroleum carbon-based resources, including methanol, CO2, CO, and biomass. For COx resources, the two main routes for producing aromatics products are discussed, i.e., the olefinic and the oxygenates-mediated route. Moreover, several improvement strategies for enhancing catalytic performance are also discussed, i.e., the addition of metal components, tuning the metal and zeolite structure, and modifying the reaction process. Finally, prospects for future development are formulated.